Çağdaş Sanatta Bir Yanılsama Tekniği: ‘Anamorfoz’ ve Felice Varini / An Illusion Technique in Contemporary Art: ‘Anamorphosis’ and Felice Varini - Kocalan, Mustafa; Türkdoğan, Tansel (Journal of History Culture and Art Research, 2018)
Abstract In the 20th century and especially in the 21st century, the theory and the concepts such as simulation', ‘manipulation', ‘illusion', 'secret' and 'reality' have been interpreted differently from old times in several disciplines especially in visual arts. Some misleading techniques within various methods and aesthetic rules have been applied in the way that they deal with these concepts which are contained in art dynamics serving as a language of visual expression. Though the performed images within ‘Anamorphosis', its alias ‘anamorphic illusion' technique which is one of the most interesting techniques, at first glance look like difficult and chaotic constructions to solve, they represent a fictitious image, space or surface with the purpose of deceiving and they also include visual effects, deformation, and utopia.In the anamorphic works that change as long as it moves and can only be resolved from a specific point and angle, they become a part of the spectator composition in order to discover the truth and meaning and thus interactive situations also occur. In this research, with an overview of the anamorphous technique’s form and development in historical process, was carried out in order to examine and evaluate the approach styles of the concept of Illusion which has modern artist Felice Varini who interprets this technique by associating with light, color, texture, mass, place, space, spacing and surface concepts. In accordance with the aim of the study, firstly the definition, types, methods and development process of the Anamorphosis technique have been examined, then some examples of Varini's work, which the first sight are perceived as having complex fragments and manipulating the perception of space at the same time have been presented and the effect of this situation on the viewer and the way of interpretation depending on the misleading features have been discussed. Öz 20. yüzyıl ve özellikle de 21. yüzyılda ‘simülasyon’, ‘manipülasyon’, ‘yanılsama’, ‘giz’ ve ‘gerçeklik’ gibi kuram ve kavramlar, başta görsel sanatlar olmak üzere çeşitli disiplinlerde önceki dönemlerden farklı biçimlerde yorumlanmıştır. Görsel anlatım diline hizmet eden sanat dinamiklerinin içinde barındırdığı bu kavramları ele alış biçimlerinde çeşitli yöntemler ve estetik kuralları dâhilinde de bazı yanıltıcı teknikler uygulanmıştır. En ilgi çekici tekniklerden biri olan ‘anamorfoz’ diğer adıyla ‘anamorfik illüzyon’ tekniği ile gerçekleştirilen görüntüler, ilk bakışta her ne kadar çözümlenmesi zor ve kaotik yapılar gibi gözükseler de yanıltma amacıyla birlikte gerçeği, imgeyi, mekânı veya yüzeyi temsil etmektedirler. Aynı zamanda bu görüntüler deformasyonu, görsel efekti ve ütopyayı da içinde barındırmaktadırlar. Hareket edildiği sürece değişen, ancak belirli bir noktadan ve açıdan çözümlenebilen anamorfik çalışmalarda gerçeği ve anlamı keşfetme yolunda, seyirci kompozisyonun parçası haline gelmekte ve bu sayede bazı interaktif durumlar da gerçekleşmektedir. Bu araştırma, anamorfoz tekniğinin biçemine ve tarihsel süreçte gelişimine genel bir bakış ile birlikte; bu tekniği ışık, renk, doku, kütle, mekân, uzam, espas ve yüzey kavramlarıyla ilişkilendirerek yorumlayan Çağdaş sanatçı Felice Varini’nin ‘yanılsama’ kavramına yaklaşım biçimlerini incelemek ve değerlendirmek amacıyla gerçekleştirilmiştir. Çalışma amacı doğrultusunda, ilk önce Anamorfoz tekniğinin tanımı, çeşitleri, yöntemleri ve gelişim süreci incelenmiş, sonrasında ise Varini’nin ilk bakışta karmaşık parçalara sahipmiş gibi algılanan ve aynı zamanda mekân algısını manipüle eden çalışmalarından bazı örnekler sunularak izleyici üzerinde yarattığı etki ve yanıltıcı özelliklerine bağlı olarak yorumlama biçimleri ele alınmıştır.